Analisis Yuridis Mengenai Kedudukan Kode Etik Bankir Dalam Dimensi Tindak Pidana Perbankan - Hatta Zul; Erwin Yulianto (Universitas Batanghari Jambi, 2021)
The purpose of this research is to formulate the implementation of a banker code of ethics in carrying out the banking employee profession to minimize the occurrence of banking crimes. The method used in this research is normative juridical, with descriptive analytical specifications, through literature study and field studies, then analyzed qualitatively non-mathematically. Conclusion with the existence of the Banker Code of Ethics, a banker is expected to be able to carry out his duties without violating existing provisions so as to avoid actions (especially criminal acts) that can harm customers.